Cohort profile: the Olmsted County hypertensive disorders of pregnancy (HDP) cohort using the Rochester Epidemiology Project - Vaughan, Lisa; White, Wendy M; Tobah, Yvonne S Butler; Kattah, Andrea; Parashuram, Santosh; Gunaratne, Madugodarlalalage D; Vermunt, Jane V; Mielke, Michelle; Milic, Natasa M; Suvakov, Sonja; Bielinski, Suzette; Chamberlain, Alanna M; et al. (BMJ open, 2022)
PurposeThe Olmsted County hypertensive disorders of pregnancy (HDP) cohort is a population-based retrospective study designed to compare the incidence of HDP on a per-pregnancy and per-woman basis and to identify associations between HDP with ageing-related diseases, as well as accumulation of multimorbidity.ParticipantsUsing the Rochester Epidemiology Project (REP) medical records-linkage system, a cohort was collected consisting of women who gave birth in Olmsted County between 1976 and 1982. After exclusions, a per-pregnancy cohort of 7544 women with 9862 pregnancies between 1976 and 1982 was identified, and their delivery information was manually reviewed. A subset of these women comprised the per-woman cohort of 4322 pregnancies from 1839 women with delivery information available throughout the entirety of their childbearing years, along with decades of follow-up data available for research via the REP.Findings to dateBy constructing both per-pregnancy and per-woman cohorts, we reported a doubling of HDP incidence rates when assessed on a per-woman basis compared with rates observed on a per-pregnancy basis. Moreover, in addition to finding that women with a history of HDP developed specific diseases at higher rates and at early ages, we also discovered that a history of HDP is associated with accelerated ageing, through accumulation of multimorbidity.Future plansIn addition to these outcomes described above, many other potential outcomes of interest for studies of HDP can be ascertained from accessing the electronic health records (EHR) and billing systems available through the REP. These data can include all International Classification of Diseases (ICD)-9 and ICD-10 and Current Procedural Terminology coded diagnoses and procedures, healthcare utilisation, including office visits, hospitalisations and emergency room visits, and full text of the EHR that is available for chart abstraction or for natural language processing of the clinical notes.